Enhancing education and skill building through eduskill program - Ahmad Dahlan, Abdul Rahman; Hasim, Siti Humairah; Mohd Nazri, Najla Fathi; Jamal Arbi Talib, Nor Ain Farhana (Research Publish Journals, 2015)
Department of Statistic has release the computer literacy rate in Malaysia and shows that the rates was increasing every year for both urban and rural area. The definition used in census was based on the ability to use computer with one of the reference that was playing computer games. The study explores the combination of education, skill and games which mainly involved in children growth development. The children nowadays are mainly exposed to the world of technology. Games are one of the results from technology development, while education and skill play an important role in our life. This objective of this study is to inquire the possibility of combining this three aspect in order to form new way of studying and developing skill of the children. Methodology that used for this paper was literature review and nine blocks of Business Model Canvas framework. With this method of studying, it is expected that the literacy rate in Malaysia can be increased and children also can learn more beneficial skill from this EduSkill program.